Internet of things system for lime planting in Maha Sarakham community - Tharach Arreerard; Woraphapa Arreerard; Naphattanon Thongpan; Niraj Ruangsan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2024)
The objectives of this research were: i) to study components of the internet of things (IoT) system to support community lime planting (CLP); in Maha Sarakham Province; ii) to develop IoT-CLP; and iii) to transfer IoT-CLP to the target community in Maha Sarakham Province. The research tools were: i) IoT-CLP system suitability assessment form; ii) IoT-CLP efficacy evaluation form; iii) a questionnaire to assess the effectiveness of the community lime planting; and iv) a survey of community satisfaction towards IoT-CLP. The research results showed that i) components of IoTCLP consist of: (1.1) data receivers: soil moisture, temperature, soil pH, fertilizer/nutrient; (1.2) control units: water supply, water spraying, soil pH control, and processing, fertilizer/nutrients; (1.3) operating systems: water supply, water spraying, soil pH communication and distribution system of fertilizer/soil nutrients water; (1.4) mobile application; ii) the effectiveness of IoT-CLP was evaluated at the highest level; and iii) the results of lime cultivation using IoT-CLP showed a higher yield than the traditional practices in terms of the amount of lime, size, and weight. The community was satisfied with IoT-CLP at the highest level.